Leveling the Intra-household Playing Field : Compensation and Specialization in Child Labor Allocation - V. Del Carpio, Ximena; Macours, Karen (2012)
This paper analyzes changes in the allocation of child labor within the household in reaction to exogenous shocks created by a social program in Nicaragua. The paper shows that households that randomly received a conditional cash transfer compensated for some of the intra-household differences, as they reduced child labor more for older boys who used to work more and for boys who were further behind in school. The results also show that households that randomly received a productive investment grant, in addition to the basic conditional cash transfer benefits, both targeted at women, show an increased specialization of older girls in nonagricultural and domestic work, but no overall increase in girls' child labor. The findings suggest that time allocation and specialization patterns in child labor within the household are important factors to understand the impact of a social program.